2018
DOI: 10.1371/journal.pone.0198526
|View full text |Cite
|
Sign up to set email alerts
|

Resistome of carbapenem- and colistin-resistant Klebsiella pneumoniae clinical isolates

Abstract: The emergence and dissemination of carbapenemases, bacterial enzymes able to inactivate most β-lactam antibiotics, in Enterobacteriaceae is of increasing concern. The concurrent spread of resistance against colistin, an antibiotic of last resort, further compounds this challenge further. Whole-genome sequencing (WGS) can play a significant role in the rapid and accurate detection/characterization of existing and emergent resistance determinants, an essential aspect of public health surveillance and response ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 82 publications
11
52
2
3
Order By: Relevance
“…Interestingly, we also identified many plasmids in the characterized isolates, especially IncF-type and although, according to Lomonaco et al [37], these mutations seem not to be related to colistin resistance. However, these two isolates showed phenotypic resistance to colistin.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Interestingly, we also identified many plasmids in the characterized isolates, especially IncF-type and although, according to Lomonaco et al [37], these mutations seem not to be related to colistin resistance. However, these two isolates showed phenotypic resistance to colistin.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, ST101 is a high-risk for mediating further spread of carbapenem resistance [34,35]. In Italy, this ST has generally been reported as sporadic [7,10,11,16,17,32], with higher prevalence when the studied strains were isolated from any infection site [34,36,37]. We found that approximately 18% of the characterized strains belonged to ST101, while no isolates belonging to this ST were identified in the report of Calia et al in Southern Italy [28].…”
Section: Discussionmentioning
confidence: 50%
“…Traditionally, colistin resistance in KP is associated with mutations in chromosomal genes [43]. Among the isolates characterized in our study, two carried the L213M substitutions in the chromosomal pmrB gene, although, according to Lomonaco et al [37], these mutations seem not to be related to colistin resistance. However, these two isolates showed phenotypic resistance to colistin.…”
Section: Discussionmentioning
confidence: 49%
“…Klebsiella pneumoniae ST14 is a major reservoir for bla OXA-232 and sometimes co-harbours bla NDM-1 [6e8]. Moreover, it has been encountered in neonatal and paediatric infections along with other plasmid-mediated antimicrobial-resistance genes, including bla KPC-2 , bla CTX-M- 15 and aac(6ʹ)Ib-cr, suggesting that this species evolves by obtaining extra plasmids in clinical environments in which diverse genes are present [9].…”
Section: Introductionmentioning
confidence: 99%